Analisis Strategi Budi Daya Maggot: Solusi Inovatif Untuk Pemberdayaan Masyarakat Desa Bojo Dan Pengelolaan Sampah Organik - Edo, Trisno; Nur, Irawati; Sudarmono (Beujroh : Jurnal Pemberdayaan dan Pengabdian pada Masyarakat, 2025)
To overcome this problem, maggot cultivation from Black Soldier Fly (BSF) flies is proposed as an innovative solution. Maggot BSF is able to quickly decompose organic waste, reduce waste buildup, and produce valuable products such as organic fertilizers (kasgot) and animal feed. This strategy not only supports waste management but also opens up new business opportunities, increase community income, as well as create environmental awareness. Through training, simple infrastructure development, and collaboration with various parties, maggot cultivation is expected to be a sustainable solution that is able to empower the people of Bojo Village while preserving the environment.